2008
DOI: 10.1158/1940-6207.capr-08-0165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Kava Chalcone Flavokawain A Differ in Bladder Cancer Cells with Wild-type versus Mutant p53

Abstract: Flavokawain A is the predominant chalcone from kava extract. We have assessed the mechanisms of flavokawain A's action on cell cycle regulation. In a p53 wild-type, low-grade, and papillary bladder cancer cell line (RT4), flavokawain A increased p21/WAF1 and p27/ KIP1, which resulted in a decrease in cyclin-dependent kinase-2 (CDK2) kinase activity and subsequent G 1 arrest. The increase of p21/WAF1 protein corresponded to an increased mRNA level, whereas p27/KIP1 accumulation was associated with the down-regu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 41 publications
8
106
0
Order By: Relevance
“…Cells were stained using 50 ”g/mL propidium iodide for 30 min. Approximately 10 000 cells per sample were analyzed by FACScan flow cytometer (BD Biosciences) and the percentage of cells in the G1, S, and G2-M phases of the cell cycle was determined using Mod-FIT software as described previously (Tang et al 2008). …”
Section: Cell Morphology Observation and Dapi Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were stained using 50 ”g/mL propidium iodide for 30 min. Approximately 10 000 cells per sample were analyzed by FACScan flow cytometer (BD Biosciences) and the percentage of cells in the G1, S, and G2-M phases of the cell cycle was determined using Mod-FIT software as described previously (Tang et al 2008). …”
Section: Cell Morphology Observation and Dapi Stainingmentioning
confidence: 99%
“…Flavokawain A, B, and C, constitute approximately 0.46%, 0.015%, and 0.012% of kava extracts, respectively (Dharmaratne et al 2002). Previous studies have shown that the chalcone flavokawain A (FKA), the predominant chalcone in kava extracts, induces apoptosis of bladder cancer cells via Bax-and mitochondriadependent apoptosis and cell-cycle arrest, and the anti-tumor action of the chalcone flavokawain B (FKB) isolated from kava extracts is even stronger than that of FKA (Zi and Simoneau 2005;Tang et al 2008Tang et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic activities of compounds 1-12 were evaluated against HEPG2 (liver) and LOVO (colon) tumor cell lines using the MTT assay (Tang et al, 2008). Compounds 8, 9 and 10 showed In conclusion, we have isolated three new diterpenoids whose chemical structures were determined based on extensive spectroscopic studies and chemical methods.…”
Section: Resultsmentioning
confidence: 99%
“…In p53 mutated cell lines, however, flavokavain A (23) prevented the G2/M transition via persistent activation of Cdk1 kinase activity and increased levels of cyclin B1, which counteracted the decreased level of Cdc25C. The Cdk1-inhibitory kinases Myt1 and Wee1 were suppressed, allowing Cdk1 to remain dephosphorylated [167].…”
Section: Chalcones As Inhibitors Of the Cell Cyclesmentioning
confidence: 99%